2014
DOI: 10.1136/bmjopen-2013-004401
|View full text |Cite
|
Sign up to set email alerts
|

Why women choose to give birth at home: a situational analysis from urban slums of Delhi

Abstract: ObjectivesIncreasing institutional births is an important strategy for attaining Millennium Development Goal -5. However, rapid growth of low income and migrant populations in urban settings in low-income and middle-income countries, including India, presents unique challenges for programmes to improve utilisation of institutional care. Better understanding of the factors influencing home or institutional birth among the urban poor is urgently needed to enhance programme impact. To measure the prevalence of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 24 publications
(26 reference statements)
10
31
0
Order By: Relevance
“…The survey included participants who had given birth in the previous 5 years. Moreover, the current study setting in the national capital of India has a better infrastructure, such as more health facilities and better accessibility to them, which may act as a promotional factor for institutional delivery [17][18][19]. A survey conducted by the Government of India (District Level Health Survey-3) included information for births in the previous 2 years and another study showed a more or less similar prevalence for the State of Delhi, India (current study area) [17,20].…”
Section: Discussionmentioning
confidence: 99%
“…The survey included participants who had given birth in the previous 5 years. Moreover, the current study setting in the national capital of India has a better infrastructure, such as more health facilities and better accessibility to them, which may act as a promotional factor for institutional delivery [17][18][19]. A survey conducted by the Government of India (District Level Health Survey-3) included information for births in the previous 2 years and another study showed a more or less similar prevalence for the State of Delhi, India (current study area) [17,20].…”
Section: Discussionmentioning
confidence: 99%
“…4 Many measures are being taken to increase the institutional delivery in India; but, some studies still report home deliveries occurring in rural and urban poor families. [5][6][7][8] According to UNICEF estimates, the institutional delivery rates are 90.9%. The remaining 9.1% are deliveries at home.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon, admitted by all stakeholder accounts for poor focused care as health staff are overburdened, with often reported episodes of health staff unfriendliness. Similar evidence from this study finding is documented (d ' Ambruoso et al, 2005;Devasenapathy et al, 2014;Larson, Hermosilla, Kimweri, Mbaruku, & Kruk, 2014;WHO, 2014). Improvements in these areas need multiple targeted responses.…”
Section: Discussionsupporting
confidence: 79%
“…Women in such family settings often lack knowledge about the risk associated with their intentions on avoiding maternal care. This finding is similar to a study among Indian women who shyed away from health staff in order to hide their parity desires from clinic staff (Devasenapathy et al, 2014). Additionally, among economically empowered women, the burden of economic, child caring and reproductive role expectations for women may cause delays for maternity care utilization.…”
Section: Discussionsupporting
confidence: 75%